The potential of fishery waste as an alternative source of natural calcium: a review - Suprihadi, Suprihadi; thaib, Azwar; Nurhayati, Nurhayati; Handayani, Lia (Universitas Malikussaleh, 2023)
Research on calcium minerals that are effective and safe for health and the environment is being developed. These studies aim to find natural ingredients that contain high mineral levels, study effective methods, and study the characteristics of calcium obtained. Natural calcium is interesting to develop because it comes from renewable natural resources such as those fishery wastes. This article contains a study of the potential of fish bones, shellfish shells, and crustacean shells as natural sources of calcium and methods of manufacture. Oyster shells that are crushed at 900°C for 2 hours will produce Ca2+ levels of 56.77% while calcination for 4 hours produces Ca2+ = 86.22%. direct shells calcined at 900°C; 4 hours yields Ca2+= 77.15%. The yield produced with a calcination time of ‰¥ 4 hours is relatively stable, which is 55 -57 %.Keywords: Calcium; Clam shells; crustacean shells; fish bones